Some Continuous Properties on Fuzzy Metric Space - Bhandari, Thaneshor (Annual Oxford Journal, 2025)
This paper deals with the concept of fuzzy metric space and their basic topological properties with illustrative examples. We define continuous mappings from a fuzzy metric space (U, F, ∗) into a fuzzy metric space (V, F, ∗) and prove some properties of continuous mappings including the composition function of two fuzzy continuous functions to be a fuzzy continuous function and the Cartesian product of two fuzzy metric space is a fuzzy metric space. To clarify the result, one numerical example is also presented.